Optimizing Programs at a State Madrasah Aliyah in Bandung to Strengthen High School Students’ Character Education - Yayah Rahyasih; Luthfi Audia Pribadi; Hega Nurazizah (STAI Hubbulwathan Duri, 2022)
The research is conducted to find out how the planning process of organizing the implementation and evaluation of character education strengthening throughout programs in madrasah education units. The role of the school’s stakeholder in designing character-based learning strategies means that a great nation is a nation that has character and has high competitiveness. Good values must be owned by a nation as a competency capital so as to be able to answer the challenges in the era of globalization. Strengthening the character of the nation is in line with the hope and commitment of the Indonesian president through the National Movement of Mental Revolution (GNRM). This commitment was followed up with the presidential decree no. 87 of 2017. This research was conducted at an Islamic-based senior high school (Madrasah Aliyah) in Bandung which has the concept of strengthening character education through two aspects, learning and extracurricular. This research is a qualitative case study which collected the data through observation studies, interviews, and documentation. For data analysis techniques, there are three steps namely data collection, data reduction, data presentation and conclusion/verification withdrawal. The results of the research found the planning of character education strengthening activities at this school integrated self-development programs through the school curriculum. Meanwhile, the implementation of strengthening character education is implemented through habits of behaviour and transparency. Evaluation activities emphasize the assessment of students' morals on the suitability of the program that has been planned.